Sensitivity of bacteria involving pediatric urinary tract infection to some available antibiotics - AA Moghadam Nia (Babol University of Medical Sciences, 1999)
Objective: Despite the availability of new highly efficient antibiotics, we encountered with many cases of bacterial resistance to microorganisms due to irrational drug administration. Methods: This cross-sectional study was performed on the urine samples of suspected patients with UTI referred to Amirkola children hospital during 1996-1998. Then antibiotic sensitivity tests with Kirby-Bauer technique on the positive cultures was carried out with some antimicrobial agents such as amikacin, gentamicin, tubramicin and nalidixic acid, ampicillin and co-trimoxazole. Findings: Among 586 patients with positive culture samples, 64.3% were girls and 35.7% were boys, and microorganisms such as E.coli (61.1%), Entrobacter (15.7%), Proteus, Staphylococcus, and Pseudomonas aeruginosa were common. However these findings, in comparison to the infants with Entrobacter urinary infection (52.6%) showed a significant difference (P<0.0001). On the bases of results, effective antibiotics were amikacin, gentamicin, tubramicin, and nalidixic acid. Conclusion: This study demonstrated that antimicrobial resistance to ampicillin and co-trimoxazole were 100% and 80% respectively.